Enhanced serum interferon-lambda 1/interleukin-29 levels in patients with psoriasis vulgaris - Li-xin Fu; Tao Chen; Zai-Pei Guo; Na Cao; Li-Wen Zhang; Pei-Mei Zhou (Sociedade Brasileira de Dermatologia, 2021)
Abstract Background: Interferon (IFN)-λ1, also named Interleukin (IL)-29, is a new member of the Type III IFN or IFN-λ family. IL-29 plays an important role in the pathogenesis of many types of autoimmune and inflammatory diseases. Objective: To study the role of IL-29 in the pathogenesis of psoriasis vulgaris. Methods: The authors detected the serum levels of IL-29 in forty-one patients with psoriasis vulgaris, twenty-three patients with atopic dermatitis and thirty-eight age and gender-matched controls by sandwich Enzyme-Linked Immunosorbent Assay (ELISA). The effects of IL-29 on the expression of cytokines, such as IL-6, IL-17, IL-8, IL-4, IL10, Interferon (IFN-γ) and Tumor Necrosis Factor-α (TNF-α), in PBMCs and HaCat cells were determined by real-time quantitative PCR. Results: Our data indicated that serum IL-29 levels were significantly elevated in patients with psoriasis vulgaris when compared with atopic dermatitis patients and the control group. Moreover, Serum levels of IL-29 were closely associated with the severity of psoriasis vulgaris. Furthermore, IL-29 up-regulated the mRNA expression levels of IL-6, IL-17 and TNF-α in PBMCs from psoriasis vulgaris patients. In addition, IL-29 enhanced the IL-6 and IL-8 expression from the HaCat cells. Conclusion: This study provides the first observations on the association of IL-29 and psoriasis vulgaris and showed elevated IL-29 serum levels. The authors suggest that IL-29 may play a role in the pathogenesis of psoriasis vulgaris.